Hyperbaric oxygen therapy as a complementary treatment for radiation proctitis: Useless or useful? – A literature review - Alpuim Costa, D (2021)
Radiotherapy (RT) is the backbone of multimodality treatment of more than half of cancer cases. Despite new modern RT techniques, late complications may occur such as radiation proctitis (RP). The natural history of RP is unpredictable. Minor symptoms may resolve spontaneously or require conservative treatment. On the other hand, for similar and uncomplicated clinical contexts, symptoms may persist and can even be refractory to the progressive increase in treatment measures. Over the last decades, an enormous therapeutic armamentarium has been considered in RP, including hyperbaric oxygen therapy (HBOT). Currently, the evidence regarding the impact of HBOT on RP and its benefits is conflicting. Additional prospective and randomised studies are necessary to validate HBOT's effectiveness in the 'real world' clinical practice. This article reviewed the relevant literature on pathophysiology, clinical presentation, different classifications and discuss RP management including a proposal for a therapeutic algorithm with a focus on HBOT.